Deconstructive and Reconstructive Techniques in Treatment of Vertebrobasilar Dissecting Aneurysms: A Systematic Review and Meta-Analysis - Sönmez, Ö. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Various endovascular techniques have been applied to the treatment of vertebrobasilar dissecting aneurysms, including parent artery preservation with coiling, stent placement or flow diverter placement, and trapping and proximal occlusion. We performed a systematic review and meta-analysis to study clinical and angiographic outcomes of patients undergoing endovascular treatment of vertebrobasilar dissecting aneurysms. MATERIALS AND METHODS: We performed a comprehensive literature search for studies on the endovascular treatment of vertebrobasilar dissecting aneurysms. From each study we abstracted the following data: immediate occlusion, long-term occlusion, long-term good neurologic outcome, perioperative morbidity, perioperative mortality, rebleed (ruptured only), recurrence, and retreatment. We performed subgroup analyses of patients undergoing deconstructive-versus-reconstructive techniques. Meta-analysis was performed by using a random effects model. RESULTS: Seventeen studies with 478 patients were included in this analysis. Sixteen studies had at least 6 months of clinical/angiographic follow-up. Endovascular treatment was associated with high rates of long-term occlusion (87.0%; 95% CI, 74.0%–94.0%) and low recurrence (7.0%; 95% CI, 5.0%–10.0%) and retreatment rates (3.0%; 95% CI, 2.0%–6.0%). Long-term good neurologic outcome was 84.0% (95% CI, 65.0%–94.0%). Deconstructive techniques were associated with higher rates of long-term complete occlusion compared with reconstructive techniques (88.0%; 95% CI, 35.0%–99.0% versus 81.0%; 95% CI, 64.0%–91.0%; P < .0001). Deconstructive and reconstructive techniques were both associated with high rates of good neurologic outcome (86.0%; 95% CI, 68.0%–95.0% versus 92.0%; 95% CI, 86.0%–95.0%; P = .10). CONCLUSIONS: Endovascular treatment of vertebrobasilar dissecting aneurysms is associated with high rates of complete occlusion and good long-term neurologic outcomes. Deconstructive techniques are associated with higher occlusion rates. There was no statistical difference in neurologic outcomes between groups, possibly due to low power.